Facilitating Deliberative Play. (July 2023) - Sprain, Leah
Craig (2023) offers deliberative play as a communicative practice that advances deliberative goals even though it is not per se deliberative. This playful interaction includes indeterminacy or uncertainty of outcome, to-and-fro movement, and an as-if ontology that can be either cooperative or competitive. I draw on the concept of deliberative play and interaction from deliberative events to generate practical theory to guide deliberative facilitators. The analysis demonstrates metacommunicative cues of the deliberative play frame, particularly even-if questions. It also contributes this to the theoretical development of deliberative play by suggesting that some of the instrumental concerns of facilitators (e.g., maintaining engagement and active participation in the creation of new meanings and actionable knowledge) might productively be considered part of deliberative play to help distinguish when to-and-fro movement stops contributing to deliberative goals. This practical theory provides facilitators ways to recognize nondeliberative interaction that can advance deliberative ends.